Green transformational and transactional leadership in fostering green creativity among university students - N. Saif; G.G.G. GOH; J.W. Ong; I.U. Khan (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The current study investigates green transactional leadership for the first time in order to understand leader-follower relations in studying green behavior in higher education institutions. The aim of this study is to investigate the dynamic relationship between green transformational leadership, green transactional leadership and green creativity that are mediated by green intrinsic motivation.METHODS: This study used adapted constructs from previous environmental research as well as a newly-developed green transactional leadership construct. Responses were obtained from university students working on their final-year projects. In order to evaluate the model, partial least squares structural equation modeling using Measurement model assessment was used to validate the structural and measurement model.FINDINGS: Findings indicate that green intrinsic motivation significantly influences the relationship between green transformational leadership and green creativity (Beta=0.321; t=3.129), as well as green transactional leadership and green creativity (Beta=0.114; t=2.322). However, green transformational leadership is a stronger predictor in comparison to green transactional leadership in nurturing green creativity among students to provide viable solutions to existing products/processes. The R2 or contribution given by green transformational leadership and green transactional leadership on green creativity was 45.7 percent while the contribution of green transformational leadership, green transactional leadership and green creativity on green intrinsic motivation was 57.7 percent.CONCLUSION: Policy makers must focus their attention on promoting green transactional and transformational leadership that will directly enhance students’ motivation to promote the green creativity through innovative product/service model innovation.